Kesantunan dalam komunikasi: Analisis teori Brown dan relevansinya dalam konteks sosial budaya - dewi, devira kumala (Maliki Interdisciplinary Journal, 2025)
This study identifies that the principle of politeness in communication plays a crucial role in maintaining the relationship between speakers and interlocutors to create effective interactions. Politeness is not only related to good intentions but also involves word choice, intonation, facial expressions, and body movements, all of which can influence the perception of the interlocutor. The primary goal of implementing politeness is to create a pleasant atmosphere for interaction and facilitate smooth communication. Effective communication is governed by various rules that reflect the social relationships between the parties involved. Several scales are used to measure the level of politeness, one of which is the scale proposed by(Brown, 1987). This scale evaluates politeness based on three main factors: (1) social distance, (2) social status between the speaker and the interlocutor, and (3) the type of speech act used. These factors are rooted in social, cultural, and situational contexts, serving as the foundation for assessing the degree of politeness in an utterance. By understanding and applying the principles of politeness, communication can occur harmoniously and effectively, fostering positive relationships between speakers and interlocutors.